2014
DOI: 10.1016/j.ijgo.2014.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of neonatal respiratory distress syndrome in term pregnancies by assessment of fetal lung volume and pulmonary artery resistance index

Abstract: The use of either FLV or PA-RI predicted neonatal RDS. The predictive value increased when these two measures were combined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
6
13
2
Order By: Relevance
“…This finding is in line with a study conducted in the Republic of China [23]. However, our finding is higher than studies conducted in several countries including Nepal (34%) [24], India (33.4%) [10], Egypt (34.3%) [25], Pakistan (4.6%) [26], Northern Italy (20.1%) [27], and Portugal (8.83%) [28]. Variance noted in these studies may have been due to differences in the study settings which maybe…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is in line with a study conducted in the Republic of China [23]. However, our finding is higher than studies conducted in several countries including Nepal (34%) [24], India (33.4%) [10], Egypt (34.3%) [25], Pakistan (4.6%) [26], Northern Italy (20.1%) [27], and Portugal (8.83%) [28]. Variance noted in these studies may have been due to differences in the study settings which maybe…”
Section: Discussionsupporting
confidence: 92%
“…Based on the current finding, the overall incidence of RD was 8.1 per 100 neonate-days (95%CI: 7.3, 8.9). The common causes of RD in our study were RDS and meconium aspiration, which is similar to previous findings from Nepal and Egypt [24,25].…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…However, our finding is higher than a study conducted in several countries reported by Nepal Medical College and Teaching Hospital 34% [23], India 33.4% [9], Egypt 34.3 [24], National Institute of Child Health, Karachi 4.6% [25], Northern Italian 20.1% [26] and Portugal (8.83%) [27].…”
Section: Discussioncontrasting
confidence: 80%
“…The deficiency of pulmonary surfactant resulting in lung prematurity is the most common cause of RDS in newborns . The incidence of newborn RDS increases with decreasing gestational age as the lungs are the final fetal organs to mature . Prediction for fetal lung maturity (FLM) plays an important role in the prevention of RDS in the preterm newborns.…”
Section: Introductionmentioning
confidence: 99%